The development of vehicular traffic intensity in Pardubice region - Horník, Tomáš; Ledvinová, Michaela (Kaunas University of Technology, 2019)
The contribution will pursue an data prognosis of vehicular traffic in the Czech republic (in region of Pardubice). The author will work with the data provided by the Road and Motorways Directorate of the Czech Republic in the context of nationwide traffic censuses. This traffic censuses were held in years 2000, 2005, 2010 and 2016. The main aim of this contribution is to offer a perspective at the development of annual average traffic intensities on the roads in the Pardubice Region. Methods of statistical analysis of data will be used during the analysis and the analysis will take into account the geographical and administrative division of the territory.
Vývoj intenzity automobilové dopravy v Pardubickém kraji
Keywords: data prognosis; development of traffic intensity; vehicular traffic; prognóza dat; rozvoj intenzity dopravy; automobilový provoz